Evaluating sorghum and maize germplasm for post-anthesis drought tolerance - Groene, Grant Anthony (Kansas State University, 2008)
Drought is the single most limiting factor in crop production. This study was conducted to investigate if a cell viability assay could serve as an effective, efficient screen to determine post-anthesis drought tolerance in sorghum (Sorghum bicolor [L.] Moench) and maize (Zea mays [L]). The assay measured decline in chlorophyll fluorescence (Fv/Fm) over time from leaf punches collected from plants grown under optimum environmental conditions and placed in an incubator under high respiratory demand. A total of 300 lines of sorghum and 197 lines of maize were screened using this assay and potential post flowering drought tolerant staygreen lines and non-stay green lines were identified. Further testing of potential lines was done in both controlled and field environments, under drought conditions, to evaluate genotype performance for physiological, yield, and staygreen traits. Standard known staygreen and non-staygreen checks were also included in these studies for comparisons. Some relationships existed between results from the cell viability assay and performance measures under controlled environment and field conditions for both sorghum and corn. However, controlled experiments were limited due to space and time constraints, and field experiments were limited due to an absence of drought during the growing season. These studies showed that the staygreen trait was not clear in the known standards under controlled environment conditions. Few of the selected lines performed better under field condition. Further testing needs to be conducted to investigate the effectiveness of a cell viability assay as a feasible indicator of drought tolerance. Experiments under field conditions at different locations and with more replications would be necessary to evaluate relations between cell viability assay and expression of drought tolerance in field conditions.
Keywords: Drought; Sorghum; Maize; Agriculture, Agronomy (0285)